Overcoming procrastination God's way why put off for tomorrow what God can do today - Parks J,Clarence; Jolley Willie (Bowie : i611 publishers, 2011)
A spiritual and practical guide to help you dig out from the past, manage the present, and enter into the future.
Includes index.
Keywords: Procrastination